Uji Efektivitas Ekstrak Umbi Bawang Putih (Allium Sativum l) terhadap Kadar Glukosa Darah Mencit (Mus Musculus) yang Diinduksi Aloksan - Sri Lestari Ramadhani Nasution; Yeni Puspawani; Sintiya Hamdi; Kezia Debora (Jurnal Keperawatan Silampari, 2022)
This study aims to test the effectiveness of garlic bulbs on alloxan-induced blood glucose levels in mice. The method used is an actual experimental pretest-posttest control group design. The study revealed that garlic extract could reduce blood glucose levels in mice (p 0.05). The most doses of garlic extract that reduced blood glucose levels in diabetic mice were 6 mg/200 g BW and 12 mg/200 g BW. In conclusion, garlic extract significantly reduced blood glucose levels in diabetic mice when administered at 6 mg/200 g BW and 12 mg/200 g BW. Keywords: Allin, Allisin, Anti Diabetes, Garlic